Empowering 21st-Century Skills through Ethno-PjBL: The Case of ‘Geplak’ in Science Education - Rahmat, Shafira Ramadhina; Tyas, Rizki Arumning; Wilujeng, Insih; Hastuti, Purwanti Widhy; Susilowati (Pendidikan IPA, FMIPA, UNP, 2025)
Developing 21st-century skills—such as critical thinking and communication—is essential to prepare students for real-world challenges, yet these skills remain underdeveloped in many science classrooms. This study investigates the effect of the Project-Based Learning (PjBL) model integrated with ethnoscience content based on the traditional food